Pengaruh Pendidikan, Pelatihan dan Disiplin Kerja terhadap Produktivitas Kerja Pegawai Sekretariat Daerah Kabupaten Halmahera Timur Provinsi Maluku Utara - Mapparenta - (Jurnal Aplikasi Manajemen, 2012)
The objective of the research is to know and to analize the influence of educational, training and work discipline to the employee work productivity and to know the variable which is more dominant influence to the employee work productivity at Regional Secretariat of East Halmahera Region. The data analysis used is descriptive and multiple linear regression analysis. The result of analysis show that the education, training and the employee work discipline significantly influence to the employee work productivity at the Regional Secretariat of East Halmahera Region. The variable which is the most dominant influence to the employee work productivity is work discipline.Keywords: education, training, work discipline, and work productivity